The Synthesis and Photoluminescence of 3C-SiC Nanorods - Ha, Huynh Thi; Cao, Dao Tran; Huy, Le Quang; Quynh, Nguyen The (Communications in Physics, 2012)
The 3C-SiC nanorods were grown by using carbothermal reduction of SiO\(_{2}\) without any catalyst. The intensive broad photoluminescence peak around 480-500 nm was observed at room temperature. The 3C-SiC nanorods with green -- blue emitting light may have great application in display devices and light emitting diodes